Lingkar lengan atas dan panjang ulna sebagai parameter antropometri untuk memperkirakan berat badan dan tinggi badan orang dewasa - Mulyasari, Indri; Purbowati, Purbowati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background: Weight (Wt) and height (Ht) can be estimated by using mid-upper arm circumference (MUAC) and ulna length (UL). The formula for estimating Wt and Ht that has been formulated is mostly using subjects not Asian especially Indonesian.Objectives : derived linear regression equations to estimate Wt and Ht from MUAC and UL for Indonesian adultsMethods : The study design was cross sectional study. Population of this study was student of Health Science and Nursing Faculty Ngudi Waluyo University. The sample consisted of 303 students 19-29 years old. Research instruments were digital weight scale, microtoise, and metline. Correlation was tested using Pearson analysis. Linear regression equations was derived from linear regression analysis.Results: Wt estimation was significantly correlated with Wt (r=0.917, p<0.0001). Ht estimation was significantly correlated with Ht (r= 0.812, p<0.0001). Estimation Wt = 2.863 MUAC (cm) – 4.019 sex -14.533 (R2=0.84, SEE=4.90). Estimation Ht = 2.525 UL (cm) – 5.828 sex + 99.384 (R2=0.66, SEE=3.92). Male=0, female = 1.Conclusion: The regression equations can be used as alternative to estimate Wt and Ht from MUAC and UL for Indonesian adults.